Non-Polynomial Spline Method for Fractional Diffusion Equation - Çağlar, Süleyman Hikmet; Çağlar, Hatice Nazan; Uçar, Mehmet Fatih; Akkoyunlu, Canan (Eudoxus Press, Llc, 1424 Beaver Trail Drive, Cordova, Tn 38016 Usa, 2012)
The one-dimensional fractional diffusion equation is studied systematically using the non-polynomial spline method. The Caputo fractional derivative is used for formulation. An example is solved to assess the accuracy of the method. The numerical results are obtained for different values (n) of equation. An effective and easy-to-use method for solving such equations is needed.
Keywords: Fractional diffusion equation; Caputo fractional derivative; non-polynomial spline; decomposition method; Fraksiyonel difüzyon denklemi; Caputo kesirli türevi; olmayan polinom spline; ayrışma yöntemi